A Critical Review of the Book Curriculum in Secondary School - Seyyed Mohammad Hossein Hosseini (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The purpose of this study is to criticize the book entitled “Curriculum in Secondary School”. Therefore, a combination of a critical book review, critical philosophical inquiry, and critical educational criticism methods was used. The case of this study was the book written by Farajollahi and Talebi and published in 2014 by the Payam Noor University Press. The tool of criticism of the mentioned book is a checklist (form) of The Iranian Council for Reviewing Books and Texts the Humanities. Qualitative content analysis was also used for data analysis. According to the findings, the strengths of the book include apparent comprehensiveness, typography, the quality of printing and binding, the content congruence with the principles and Foundations of religion and Islam, the use of scientific tools, and equivalence and application of specialized terms. Shortcomings of this book include: Inappropriate cover design, need for scientific and literary editing, inappropriate overall and intra-section coherence, resource ambiguity, lack of scientific analysis, no innovation and no new content, the inconsistency of book’s content with the foundations and presuppositions of the curriculum area and non-Coverage of the approved syllabus of Ministry of Science, Research and Technology.